National Allegory in Teju Cole’s Open City - Derek F. DiMatteo (European Journal of American Studies)
This article analyzes Teju Cole’s Open City as a political novel, arguing that Open City functions as a national allegory critical of the United States. This stance is facilitated by its portrayal of the protagonist Julius as suffering not a dissociative fugue but a dissociative amnesia, which I arrive at by using the American Psychiatric Association’s Diagnostic and Statistical Manual (DSM) V and a rereading of Ian Hacking to revise prior interpretations of Julius as flâneur-fugueur. Drawing on the work of Fredric Jameson, I read Julius’s amnesia-like repression of his past crimes as allegorical of his adopted nation, the USA, which tends to forget its responsibility for its own historical injustices. By selectively forgetting these injustices and traumas—even as they happen—the USA behaves with the same dissociative amnesia as Julius. Open City reflects the psychopathology of the USA on the scale of the individual and the city. Within the palimpsests of history scattered materially throughout Manhattan (and within the repressed memories of society and the individual) resides the location of national allegory in Open City.